Prospek dan Tantangan pengembangan Industri Pulp dan Kertas Indonesia dalam Era Ekolabeling dan Otonomi Daerah - F Gunarwan Suratmo (Jurnal Manajemen Hutan Tropika, 2000)
The history and purpose of Ecolab ling system should be understand and also the relation with ISO 9000 and ISO 14000 and then the problems of Agribusiness development on pulp and paper production con be predicted in the district otonomi system. Capacity building and educated manpower in the district level should be improved. Negative impact of ecolabel system in International Trade Should be avoided. National ecolabel institute will be more favourable then international ecolabel institute.